Planificación de la revaloración patrimonial de la cerámica de la comunidad de Araypallpa, distrito de Colcha, provincia de Paruro - Bombilla Saire, Claudina (2020)
ABSTRACT This investigation work had as principal aim to determine how to plan the revaluation Patrimony of the Ceramics of the Araypallpa community of the Colcha district, Paruro Province, taking into account the perceptions of the villager regarding ceramics as cultural heritage. The investigation type is basic as the purpose that it look for; and, according to the level of knowledge acquired is descriptive. The investigation design is a not experimental transversal. The population was shaped by all the villager of Araypallpa community. The sample was shaped by 87 settlers that is the sample population. The sustained inquiry materialized in the achievement of the following specific aims: To determine the perception level of the Araypallpa community on the patrimonial value of the ceramics and to establish improvement mechanisms within the municipal management of the province of Paruro on the planning of the revaluation of the heritage of Ceramics of the Community of Araypallpa, Colcha district, Paruro Province. The main results show a very low level of perception about cultural heritage in the Araypallpa community with very bad state of cultural manifestations, no plans for its value and/or recovery. There are few people left with ancestral wisdom and technique. There is no infrastructure of basic services and adequate facilities. There is a lack of interest from the institutions to motivate interest or need for the use of this ceramic. The Araypallpa ceramic is so different and unique, it is clearly utilitarian, of domestic use, without additives foreign to the raw material that exists in its deposits, without technology, it keeps intact the ancestral technique. The Araypallpa ceramic is unique, purely rustic, without iconographies, its main characteristic is to be used daily, functional and domestic utilitarian. The purchase of the product (Araypallpa ceramics would be of great benefit to users framed in a healthy eating consumption). Finally, it also proposed guidelines based on strategic actions that range from the formation of associations of potters, branding, management of propaganda inputs, identification and mapping of actors involved, management of internal and external communication around the Araypallpa Ceramics, financing management with the relevant actors.